Creative Destruction During Crises : An Opportunity for a Cleaner Energy Mix - Deb, Pragyan (IMF Working Papers; Working Paper, 2021)
Lockdowns resulting from the COVID-19 pandemic have reduced overall energy demand but electricity generation from renewable sources has been resilient. While this partly reflects the trend increase in renewables, the empirical analysis presented in this paper highlights that recessions result in a permanent, albeit small, increase in energy efficiency and in the share of renewables in total electricity. These effects are stronger in the case of advanced economies and when complemented with environment and energy policies-both market-based measures such as taxes on pollutants, trading schemes and feed-in-tariffs, as well as non-market measures such as emission and fuel standards and R and D investment and subsidies-to incentivize and hasten the transition towards renewable sources of energy.